Ground level disturbance from large aircraft flying at supersonic speeds - Lilley, G. M.; Spillman, J. J. (College of Aeronautics, 1960)
The Whitham-Walkden theory for the estimation of the strength of shock waves at ground level from aircraft flying at supersonic speeds is applied to the case of a typical projected supersonic civil transport aeroplane. If a figure of 2 lb/sq.ft. (including a factor of 2 for ground reflection) is taken as an upper limit for the acceptable strength of the bow wave from such an aircraft it is shown that restrictions on the climb and flight plan will be involved. The advantage of the employment of larger engines with or without afterburning is discussed, with reference also to the penalties involved owing to the increase in weight of the aircraft and its direct operating costs. Finally it is suggested that an aircraft of given volume could be designed, by suitable choice of thickness and lift distribution, to minimise the strength of the shock waves in the far field.